Development of Learning Program Based on Multiple Representations Integrated with PjBL-STEM to Foster Students' Sustainability Literacy - Deni Anggraini; Abdurrahman Abdurrahman; Kartini Herlina (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2022)
This study aims to describe the validity, practicality and effectiveness of a learning program based on multiple representations integrated PjBL STEM to foster students' sustainability literacy. This study used a mix method using the ADDIE model for learning program development framework. The research subjects were the students of SMAN 2 Kotabumi, class XI MIPA 3 as the experimental class and class XI MIPA 2 as the control class. Based on the analysis of research data the learning program developed is feasible to be implemented based on the assessment of experts who meet the very valid category, has a good practicality and proved to be effective in increasing the learning outcomes of sustainability literacy with N gain in the experimental class which is higher than the control class. The study findings showed that (1) the learning program with Multiple representations integrated with PjBL STEM is proven to maximize the potential of students and minimize learning gaps because students were more facilitated to develop their potential to the fullest, (2) the Learning activities have improved students’ sustainability literacy related to renewable energy. These findings gave empirical evidence that project-based learning are recommended to support learning activities, and in line with government policy